2012
DOI: 10.1128/aem.07880-11
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Enzymatic Profiling of Pleurotus ostreatus Laccase Genes in Submerged and Solid-State Fermentation Cultures

Abstract: ABSTRACTThe genome of the white rot basidiomycetePleurotus ostreatusincludes 12 phenol oxidase (laccase) genes. In this study, we examined their expression profiles in different fungal strains under different culture conditions (submerged and solid cultures) and in the presence of a wheat straw extract, which was used as an inducer of the laccase gene family. We used a reverse transcription-quantitative PCR (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 53 publications
2
83
0
3
Order By: Relevance
“…In PC15 genome, 9 genes were detected to encode manganese-peroxidase (mnp1-mnp9) (Salame et al, 2012), just one of them (mnp3) had the structure of SSR. Phenol oxidase (laccase) is another kind of enzyme especially for fungi to degrade lignin (Castanera et al, 2012). For 12 genes encoding laccase (lacc1-lacc12) in PC15 genome, just one of them (lacc1) contained the SSR segment.…”
Section: Functional Enrichment Analysis For the Subset Of Genes Contamentioning
confidence: 99%
“…In PC15 genome, 9 genes were detected to encode manganese-peroxidase (mnp1-mnp9) (Salame et al, 2012), just one of them (mnp3) had the structure of SSR. Phenol oxidase (laccase) is another kind of enzyme especially for fungi to degrade lignin (Castanera et al, 2012). For 12 genes encoding laccase (lacc1-lacc12) in PC15 genome, just one of them (lacc1) contained the SSR segment.…”
Section: Functional Enrichment Analysis For the Subset Of Genes Contamentioning
confidence: 99%
“…Luis et al (2005) found different expression levels of laccase genes in basidiomycetes isolated from soil. Castanera et al (2012) examined the expression profiling of laccases of different strains of P. ostreatus and found that the activity and expression of these enzymes depend on the strain used in solid state fermentation and in SmF. Several studies have been carried out in order to know the enzymatic inductor type and the enzymatic inductor concentration as well as the composition of the culture medium to increase the laccases activity, however, there is very little information on the effect of the initial pH of the growing medium on the molecular and enzymatic aspects of laccase of P. ostreatus.…”
Section: Introductionmentioning
confidence: 97%
“…[10] Lacc2 and Lacc10 are highly expressed under submerged conditions. [11,27] Previous work in our lab showed that laccase activity and the degree of induction differed among different P. ostreatus strains isolated from different districts in China (unpublished data). A similar result was obtained in Flammulina velutipes.…”
Section: Introductionmentioning
confidence: 99%